Roflumilast alleviates lung injury in rats with pneumococcal pneumonia (Jichu yixue yu linchuang)
Objective To investigate the effect of roflumilast on pulmonary injury induced by Streptococcus pneumonia (SP) in rat model. Methods Rats were randomly divided into control group, pneumonia model group, roflumilast low dose group, high dose group and roflumilast high dose plus Colivelin (STAT3 activator) intervention group. The level of PaO2, PaCO2, IL-1β, IL-8, IL-10 and TNF-α were detected. Lung tissue wet/dry ratio (W/D), MDA content, MPO and SOD activity were examined. HE staining microscopy was used to observe the pathological injury of lung tissue. Apoptosis, cleaved caspase-3, IL-6, and p-STAT3/STAT3 protein expression were detected. Results Compared with the control group, the lung tissue of animals in the model group showed obvious damage; blood PaO2, oxygenation index(OI), lung tissue IL-10 level, and SOD activity were all significantly reduced; the level of blood PaCO2, lung tissue IL-1β, IL-8, TNF-α and W/D values, MDA content, MPO activity, cell apoptosis rate, cleaved caspase-3, IL-6, and p-STAT3/STAT3 protein expression were significantly increased(P＜0.05). Compared with the model group, the lung tissue damage of rats in the low and high dose groups of roflumilast was obviously reduced; the level of blood PaO2, OI and, lung tissue IL-10, and SOD activity were obviously increased, the level of blood PaCO2, lung tissue IL-1β, IL-8, TNF-α and, W/D values, MDA content, MPO activity, cell apoptosis rate, cleaved caspase-3, IL-6, and p-STAT3/STAT3 protein expression were significantly reduced(P＜0.05); Colivelin was able to partially reverse the improvement effect of roflumilast on lung injury in rats with SP pneumonia (P＜0.05). Conclusions Roflumilast may inhibit inflammatory response, oxidative damage and apoptosis of SP-induced pneumonia in rats resulting in an improvement of lung function.